2019
DOI: 10.1111/jcal.12377
|View full text |Cite
|
Sign up to set email alerts
|

Community building and knowledge sharing by individuals with disabilities using social media

Abstract: The use of social media to share information, enhance learning, and connect with an online community has grown rapidly over the past 10 years. As social media becomes a more common tool in both formal and informal education, it is imperative to understand how it is used by individuals with disabilities. Through a systematic study of the literature, 215 articles on social media used by individuals with disabilities were selected and 29 selected for in-depth thematic analysis. Six major themes were identified: c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 41 publications
(53 reference statements)
2
24
0
3
Order By: Relevance
“…After analysing the interviews collected from a group of 15 subjects, they found that the use of social media helped them to build social support and health psychological dispositions. The results of the systematic literature review performed by Sweet et al revealed that there are many reports indicating the positive aspects of social media use by people with disabilities, including gaining knowledge, forming friendships and creating social support groups [41].…”
Section: Discussionmentioning
confidence: 99%
“…After analysing the interviews collected from a group of 15 subjects, they found that the use of social media helped them to build social support and health psychological dispositions. The results of the systematic literature review performed by Sweet et al revealed that there are many reports indicating the positive aspects of social media use by people with disabilities, including gaining knowledge, forming friendships and creating social support groups [41].…”
Section: Discussionmentioning
confidence: 99%
“…Social media have the potential to support many useful activities for people with disabilities, including social and informational (Caton; Chapman, 2016; Ellis; Kent, 2016; McNeil; Brna; Gordon, 2012). Interpersonal interactions on the social web can help people with disabilities to form identities and communities through connections with likeminded others (Miller, 2017;Sweet;LeBlanc;Stough;Sweany, 2020), to gain support against bullying (Sweet; LeBlanc; Stough; Sweany, 2020) and publish their own self-descriptions and narratives (Gale; Bolzan, 2016). This can extend to online activism, coordinating and publicising through social media sites (Pearson;Trevisan, 2015) and blogs (Trevisan, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Future research should capture more exposure data and identify the behavioral responses to advertisements between heavy and light users of social media. Although heavy social media use concerns parents and researchers alike [13,34] [35], especially for marginalized groups seeking connectedness and acceptance [36][37][38][39][40][41].…”
Section: Principal Findingsmentioning
confidence: 99%